2007
DOI: 10.1590/s0103-90162007000600013
|View full text |Cite
|
Sign up to set email alerts
|

Production of streptomycete inoculum in sterilized rice

Abstract: Actinomycetes are important plant disease control and growth promotion agents, which makes it necessary to develop technology to produce large quantities of inoculum for green-house and field work. The present study had the objective of evaluating the growth of several isolates of Streptomyces in sterile rice for inoculum production. The sterile rice was inoculated with isolates of S. thermotolerans, S. griseus subsp. griseus, Streptomyces sp. N0035, S. purpurascens, and Streptomyces sp., and incubated at 28 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Pathogen inoculum was prepared following the method of Soares et al [ 61 ]. For this, 300 g of rice grains were soaked in 500 mLof distilled water at room temperature for one hour for proper hydration.…”
Section: Methodsmentioning
confidence: 99%
“…Pathogen inoculum was prepared following the method of Soares et al [ 61 ]. For this, 300 g of rice grains were soaked in 500 mLof distilled water at room temperature for one hour for proper hydration.…”
Section: Methodsmentioning
confidence: 99%
“…In order to reduce the use of chemicals for mass production, several cost-effective substrates have been tested successfully. For instance, Soares et al (2007) and Diraviyam et al (2011), have shown that sterile moistened rice, rice bran, wheat bran and sugarcane residues can be viable methods for inoculum mass production of Actinobacteria. Despite of this innovation, research must be continued to test natural, inexpensive and available products for microbial biomass production.…”
Section: Optimization Of Actinobacteria For Mass Productionmentioning
confidence: 99%
“…The culture was centrifuged at 60009g for 5 min. The cell pellet was suspended in 0.85 % saline and the cell density was adjusted to 1.0 9 10 8 CFU mL -1 using spectrophotometer at 610 nm [19]. For mass production of pathogen, inoculum was prepared by growing R. solani in wheat bran (700 g in capacity flask; moisture level 50 %) and incubated for two weeks in the dark with proper mixing at regular intervals for uniform distribution of fungal mycelia.…”
Section: Preparation Of Microbial Inoculumsmentioning
confidence: 99%